2019
DOI: 10.3390/ijms20153630
|View full text |Cite
|
Sign up to set email alerts
|

Function of Green Tea Catechins in the Brain: Epigallocatechin Gallate and its Metabolites

Abstract: Over the last three decades, green tea has been studied for its beneficial effects, including anti-cancer, anti-obesity, anti-diabetes, anti-inflammatory, and neuroprotective effects. At present, a number of studies that have employed animal, human and cell cultures support the potential neuroprotective effects of green tea catechins against neurological disorders. However, the concentration of (−)-epigallocatechin gallate (EGCG) in systemic circulation is very low and EGCG disappears within several hours. EGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(106 citation statements)
references
References 72 publications
(120 reference statements)
1
105
0
Order By: Relevance
“…Compared with our previous work [19], galangin is more cytotoxic to the two platinum-resistant ovarian cancer cells than cisplatin. Previous studies reported that flavonoids could hardly reach low micromolar levels in plasma and organs due to their low bioavailability [20]. For future studies, some strategies, such as nanoemulsion and nanoliposome [21], should be used to increase the bioavailability of galangin.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with our previous work [19], galangin is more cytotoxic to the two platinum-resistant ovarian cancer cells than cisplatin. Previous studies reported that flavonoids could hardly reach low micromolar levels in plasma and organs due to their low bioavailability [20]. For future studies, some strategies, such as nanoemulsion and nanoliposome [21], should be used to increase the bioavailability of galangin.…”
Section: Discussionmentioning
confidence: 99%
“…Although the main criticism for its therapeutic use, not only for the green extract polyphenols but also for all other dietary polyphenolic compounds, is their low bioavailability [46,47]. In this regard, different aspects must be taken into account that strengthen their potential therapeutic use (for example, some metabolites related to these compounds have therapeutic properties, among others) [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding therapeutic potential of green tea extracts, most works have focused on its main component, epigallocatechin gallate, which constitutes around 50%-65% of the total content. Catechin represents only around 1%-4% of most green tea extract, whereas total polyphenolic content of polyphenon-60 is around 80%-90% [48,[64][65][66]. Other works also show neuroprotective effects for catechin, in which oxidative stress counteraction has been postulated as the main underlying mechanism [30,67].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular signaling pathways regulated by green tea catechols resulting in their pro-apoptotic and anti-proliferative effects include, among others, inhibition of nuclear factor-κB (NF-κB) which is the crucial oxidative stress-sensitive transcription factor [14,35] NF-κB plays a critical role in the regulation of a variety of genes important in cellular responses, including inflammation, proliferation and cancer cell death. In addition, catechins contained in green tea, and above all the main catechin EGCG, activate endothelial nitric oxide synthase (eNOS) [42,47].…”
Section: Anticancer Potential Of Green Tea Catechins Based On In Vitrmentioning
confidence: 99%
“…There is a lot of in vivo evidence confirming that consumption of green tea in the form of a drink or dietary supplement exerts the anticancer properties [43,47,54]. The other valuable properties of green tea catechols involve their anti-viral, anti-bacterial, anti-aging, and hypotensive effects [4,5,9,12,27].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%